The gut commensal Faecalibacterium hominis attenuates indole—AhR signaling and restores ASD—like behaviors with BTBR mice - Yu, You; Wang, Yujing; Zhang, Jie; Li, Shucheng; Wang, Yulin; You, Xin; Chen, Xue; Du, Mengxuan; Xie, Lisheng; Liu, Shuang-Jiang (Frontiers in Microbiology, 2025)
Autism spectrum disorders (ASD), a group of neurodevelopmental disorders characterized by the core symptoms of impaired social communication and stereotyped behaviors, is strongly associated with dysregulated microbiota-gut-brain axis. Emerging evidence suggests that Faecalibacterium, which showed reduced abundance in ASD cohorts, holds therapeutic potential, though its interaction with host remain unexplored. Here, we investigated the efficacy and molecular basis of Faecalibacterium hominis 4P-15 (4P-15) in BTBR T+Itpr3tf/J (BTBR) mice, an idiopathic ASD mouse model. Oral administration of 4P-15 significantly reduced the intestinal levels of indole, indole-3-propionic acid (IPA), and indole-3-acetic acid (IAA), as well as the level of IPA in brain. Furthermore, the decreased levels of IPA in brain contributed to the attenuated aryl hydrocarbon receptor (AhR) signaling characterized by increased expression of downstream elements, including glutamate transporters and GABA receptors. Ultimately, this modulation led to the restoration of excitatory/inhibitory imbalance, a typical pathophysiological feature of ASD, and thereby alleviated ASD core behavioral symptoms. Our findings underscore Faecalibacterium-mediated AhR modulation as a promising therapeutic strategy for ASD, highlighting the dual potential of Faecalibacterium-based probiotics and targeted interventions against indole-AhR signaling to address neurodevelopmental disorders.